Negative Urgency Mediates the Relation Between Genetically Influenced Serotonin Functioning and Alcohol Problems. (January 2018) - Wang, Frances L.; Chassin, Laurie
Serotonin (5-HT) functioning is associated with alcohol problems. However, the mechanisms underlying this association remain unclear. In the current study the authors tested whether five separate dimensions of impulsivity (UPPS-P) mediated the relation between a polygenic score indexing 5-HT functioning and alcohol problems and whether any of these paths were moderated by age. Results showed that a 5-HT polygenic score predicted alcohol problems indirectly through negative urgency, but not any other facet of impulsivity. The 5-HT polygenic score also directly predicted alcohol problems. No age moderation was found. Findings suggest that negative urgency might be one important mechanism underlying the relation between genetically influenced 5-HT functioning and alcohol problems. However, genetically influenced 5-HT functioning likely influences alcohol problems through additional mechanisms. More broadly, results suggest that the previously observed transdiagnostic nature of 5-HT functioning on diverse types of psychopathology might be, in part, explained by its effect on negative urgency.